2005
DOI: 10.1002/cbf.1275
|View full text |Cite
|
Sign up to set email alerts
|

A study of glutathione status in the blood and tissues of patients with breast cancer

Abstract: Glutathione plays an important role in the antioxidant system that is required for the maintenance of the redox status of the cell, defence against free radicals and detoxification of toxic compounds. Reduced glutathione (redGSH) can be converted to oxidized glutathione (GSSG) during oxidative stress. The ratio of redGSH/total glutathione can be regarded as an index of the redox status and a useful indicator of disease risks. We conducted experiments by the capillary zone electrophoresis method to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 16 publications
6
68
0
1
Order By: Relevance
“…A previous study indicated that elevated oxidative status arising from the imbalance between reactive oxygen species (ROS) and antioxidant systems played an important role in carcinogenesis (Wu, 2006), a finding consistent with other studies that observed increased oxidative stress in patients with breast cancer (Yeh et al, 2005(Yeh et al, , 2006. ROS are a family of molecules that include highly reactive free oxygen radicals produced in all cells during oxygen metabolism.…”
supporting
confidence: 63%
“…A previous study indicated that elevated oxidative status arising from the imbalance between reactive oxygen species (ROS) and antioxidant systems played an important role in carcinogenesis (Wu, 2006), a finding consistent with other studies that observed increased oxidative stress in patients with breast cancer (Yeh et al, 2005(Yeh et al, , 2006. ROS are a family of molecules that include highly reactive free oxygen radicals produced in all cells during oxygen metabolism.…”
supporting
confidence: 63%
“…The other plausible explanation for decreased levels of glutathione observed in head and neck cancer patients is possibly GSH, being exhausted as a main low molecular weight antioxidant in cellular protection [15,16]. Our results are in agreement with earlier studies which showed that levels of glutathione decrease in blood of the breast cancer when compared with control subjects [17].…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative stress causes profound alterations of various biological structures, including cellular membranes, lipids, proteins and nucleic acids. Oxidative stress is considered to be involved in ageing (14)(15)(16)(17)(18)(19)(20) Redox status expressed as GSH:GSSG ratio as a marker for oxidative stress in paediatric tumour patients (36)(37)(38)(39)(40)(41)(42)(43)(44). There is an increasingly growing interest in identifying biomarkers for diseases, in which oxidative stress is involved (45).…”
Section: Introductionmentioning
confidence: 99%